ENVIRONMENTAL GEOCHEMICAL INVESTIGATION OF THE GEOGENIC POLLUTION POTENTIAL OF BIDA FORMATION, NORTHERN BIDA BASIN NIGERIA - Waziri, Nuhu Musa; Abakpa, James Egba; Goro, Isah Aliyu; Ahmed, Sidi Aliyu (FUDMA JOURNAL OF SCIENCES, 2023)
The environmental geochemistry of sandstones of Bida formation around Doko, northern Bida Basin Nigeria was studied to assess the potential for the release of toxic elements into the environment. Eight representative samples were collected and analysed to determine the total elemental concentration using X-ray fluorescence spectrometry (XRF). Four sub-samples were analysed for their near-total concentration of selected metals using atomic absorption spectrometry (AAS). The results show that many of the elements are depleted with mean enrichment ratios of less than 1. Ce, W, Nb and Pb are the exceptions with ER values of 116.4, 122.9, 25.26 and 2.22 respectively. A similar pattern was found with Igeo, where W, Ce and Nb fall within strongly to extremely polluted and extremely polluted classes. High to very high partition coefficients (KDi) for four selected PTEs show that metals are strongly held within the sandstone matrix rather than dissolving.  Because the elements are not soluble, they will not be readily available for uptake by plant roots, or will not be directly toxic to soil biota. The undissolved metal pool also reflects the sandstone metal fraction that is unsusceptible to leaching and could therefore not contaminate water. We conclude that there is no significant geogenic pollution risk associated with PTE release and uptake from the formation. It is however recommended that further research should be carried out to investigate the phases hosting Ce, W, Nb and Zr in the sandstone in Doko and its environs.
Keywords: Mobility; Geochemistry; Natural contamination; Sedimentary rocks; Trace elements